1964
DOI: 10.1042/bj0930260
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver nucleotide concentrations in experimental liver injury. 1. Carbon tetrachloride poisoning

Abstract: A. S. HALLSWORTH 1964 3. The c-amino group availabilities of the 640A, 220A' and structureless fibrils were also identical (69-5 %) on dinitrophenylation at higher ionic strengths.4. When dinitrophenylated in water, the proportions of reactive c-amino groups in the 640A and the two long-spacing aggregates were considerably less (approx. 44 %) than those of the same aggregates in 1 % sodium chloride.5. As the ionic strength of the aqueous dinitrophenylation medium was decreased, the molar ratio of lysyl to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Rees & Sinha (1960) showed that after CC14 there was a sharp rise in the concentration of several intracellular enzymes in the circulating blood. However, Slater, Strauli & Sawyer (1964) have recently shown that, in spite of the leakage of these enzymes of high molecular weight, NAD+ and NADH, which are mainly cytoplasmic in liver, remained firmly within the liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rees & Sinha (1960) showed that after CC14 there was a sharp rise in the concentration of several intracellular enzymes in the circulating blood. However, Slater, Strauli & Sawyer (1964) have recently shown that, in spite of the leakage of these enzymes of high molecular weight, NAD+ and NADH, which are mainly cytoplasmic in liver, remained firmly within the liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action is thought to involve the P450 cytochrome enzyme 2E1 with the production of an active metabolite ( Hubner 1965; Recknagel & Ghoshal 1966a; ; Slater et al . 1964 ).…”
Section: Pharmacological Modelsmentioning
confidence: 99%
“…However, damage in adult rats was extensive and was found to be proportional to the dose of CCl 4 administered, but massive in the enzyme induced group. The mechanism has been postulated to involve free radicals ( Slater et al . 1964 ; Recknagel & Ghoshal 1966b; Benedetti et al .…”
Section: Pharmacological Modelsmentioning
confidence: 99%
“…There is a fair amount of evidence that lysosomes are concerned with the process of intracellular digestion and are involved in various physiological and pathological pheno mena of autolysis and necrosis (2). Much biochemical work has been done in attempts to elucidate the pathogenesis of the liver injury produced by CC14 (3)(4)(5). It is known that administration of a suitable dose of CCl4 to rats results in a severe centrilobular type of necrosis and fatty degeneration of the liver (6), profound metabolic disturbances such as changes in the hepatic level of enzymes (7) and defective protein synthesis in the injured liver (8,9).…”
mentioning
confidence: 99%